Water-based anticorrosive wear-resistant paint and preparation method thereof
By combining the modified MXene nanosheets with aqueous epoxy resin emulsion and adding appropriate amounts of polytetrafluoroethylene powder, titanium dioxide, alumina and other materials, a high corrosion resistance and high wear resistance water-based coating was prepared, which solved the existing solution. The shortcomings of water-based coatings in terms of corrosion resistance and wear resistance have achieved environmentally friendly, stable and high-performance coating preparation.
Patent Information
- Application Number
- CN202411716234.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing water-based coatings have shortcomings in corrosion and wear resistance, making it difficult to effectively protect metal surfaces from corrosion and wear.
Modified MXene nanosheets are mixed with aqueous epoxy resin emulsion, and polytetrafluoroethylene powder, titanium dioxide, alumina and other materials are added under stirring conditions. Through uniform mixing and ultrasonic dispersion, a high corrosion resistance and wear resistance are prepared. Water-based anti-corrosion and wear-resistant coating.
It is possible to prepare water-based coatings with good corrosion resistance, shielding and wear resistance without polluting the environment, which significantly improves the stability and corrosion resistance of the coating.
Smart Images

Figure BDA0005156938970000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of material anti-corrosion, and in particular to a water-based anti-corrosion and wear-resistant coating and a preparation method thereof. Background Art
[0002] Metal corrosion is a phenomenon in which metals are destroyed by chemical or electrochemical effects of environmental media. The main object of corrosion is metal, among which steel is the most serious. Today, corrosion has brought huge losses to the national economy. There are many ways to prevent corrosion, such as adding other metals to make alloys, applying coatings on the metal surface for isolation, plating metals that are not easily corroded on the metal surface, and oxidizing dense oxide films on the metal surface. Among them, the method of applying coatings on the metal surface for isolation is the easiest to implement because of its easy operation and low cost. The commonly used method is to apply coatings to the protected metal surface for protection. The coatings mainly include water-based coatings and solvent coatings. The former uses water as a solvent, while the latter mainly uses organic solvents as solvents. Therefore, compared with solvent coatings, water-based coatings are low VOC (volatile organic compounds) or VOC-free environmentally friendly green coatings. At a time when people's environmental awareness is gradually increasing and they pay more and more attention to their own health, the use of water-based coatings instead of traditional solvent-based coatings has received more and more attention. There are many types of water-based coatings, and some water-based coating products have been put into use, but the current water-based coatings are slightly insufficient in terms of corrosion resistance and wear resistance. Therefore, it is necessary to develop a wear-resistant and corrosion-resistant water-based coating. Summary of the invention
[0003] The present application provides a water-based anti-corrosion and wear-resistant coating and a preparation method thereof, so as to solve the problem that the above-mentioned existing water-based coatings are slightly insufficient in terms of anti-corrosion and wear resistance.
[0004] In a first aspect, the present application provides a method for preparing a water-based anticorrosion and wear-resistant coating, comprising the following steps:
[0005] a) uniformly mixing the modified MXene nanosheets and the aqueous epoxy resin emulsion to obtain a premixed emulsion;
[0006] b) adding polytetrafluoroethylene powder, titanium dioxide, aluminum oxide, substrate wetting agent, dispersant, defoamer, surface adhesion promoter, deionized water and curing agent to the premixed emulsion in sequence under stirring, and mixing evenly to obtain a water-based anticorrosive and wear-resistant coating.
[0007] The present application provides a method for preparing a water-based anti-corrosion and wear-resistant coating, which has the following beneficial effects:
[0008] 1) The method of the present application is completed in the water phase when preparing the coating, thereby reducing the emission of organic gases and having the characteristics of being green and environmentally friendly without polluting the environment.
[0009] 2) In the method of the present application, the polytetrafluoroethylene powder added when preparing the coating can improve the anti-corrosion performance of the coating, the added titanium dioxide powder can provide the coating with good hiding power, coloring and thickness support, and the addition of aluminum oxide can improve the dispersion of the coating. The above materials are used in combination with substrate wetting agents, dispersants, defoaming agents, and surface adhesion promoters to make the coating have good stability, hiding power and anti-corrosion performance.
[0010] 3) The method of the present application adds modified MXene nanosheets and uses them together with corresponding ingredients, which can effectively improve the corrosion resistance and wear resistance of the coating.
[0011] 4) The method of the present application has simple operation steps, mild preparation conditions and is easy to implement.
[0012] Optionally, by weight, the aqueous epoxy emulsion is 20 to 50 parts, the polytetrafluoroethylene is 1 to 3 parts, the TiO2 is 2 to 5 parts, the Al2O3 is 2 to 7 parts, the substrate wetting agent is 1 to 3 parts, the dispersant is 0.5 to 3 parts, the defoaming agent is 0.1 to 3 parts, the surface adhesion promoter is 0.1 to 3 parts, the deionized water is 25 to 35 parts, and the curing agent is 3 to 5 parts.
[0013] Optionally, the modified MXene nanosheets are prepared as follows:
[0014] Dispersing MXene nanosheets in an ethanol solution, adding a silane coupling agent, reacting at 80-90°C for 24-30 hours, then centrifuging and washing the reaction mixture, and freeze-drying the modified MXene nanosheets obtained by centrifugation for 48-56 hours to obtain modified MXene nanosheets;
[0015] The mass ratio of MXene nanosheets to silane coupling agent is 1:15-30;
[0016] Types of MXene nanosheets include Ti3C2Tx-MXene, Nb2CT x -Mxene type, V2CT x -Mxene type or Mo2CT x -Mxene type.
[0017] Optionally, the silane coupling agent includes γ-aminopropyltriethoxysilane.
[0018] Optionally, the substrate wetting agent includes one or more of BYK-3400, BYK-3455, and BYK-301.
[0019] Optionally, the dispersant includes one or more of BYK-154, BYK-021, BYK-028, and BYKJET-9175.
[0020] Optionally, the defoaming agent includes one or more of BYK-1785, BYK-022, BYK-1724, and BYK-1710.
[0021] Optionally, the adhesion promoter includes one or more of BYK-4509, BYK-4500, and BYK-4513.
[0022] Optionally, pigments and fillers are also added in step b);
[0023] The amount of pigment and filler added is 1 to 3 parts by weight;
[0024] Pigments and fillers include red iron oxide, molybdenum disulfide or carbon black.
[0025] In a second aspect, the present application provides a water-based anti-corrosion and wear-resistant coating, which is prepared by any of the methods provided above.
[0026] The characteristics and beneficial effects of the water-based anti-corrosion and wear-resistant coating provided in the present application are as described in the preparation method of the first aspect above, and will not be repeated here. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.
[0028] In a first aspect, the present application provides a method for preparing a water-based anticorrosion and wear-resistant coating, comprising the following steps:
[0029] a) uniformly mixing the modified MXene nanosheets and the aqueous epoxy resin emulsion to obtain a premixed emulsion;
[0030] b) adding polytetrafluoroethylene powder, titanium dioxide, aluminum oxide, substrate wetting agent, dispersant, defoamer, surface adhesion promoter, deionized water and curing agent to the premixed emulsion in sequence under stirring, and mixing evenly to obtain a water-based anticorrosive and wear-resistant coating.
[0031] In the present application, the process of uniformly mixing the modified MXene nanosheets with the aqueous epoxy resin emulsion is: after the amino-modified MXene nanosheets are made into a dispersion, they are mixed with the aqueous epoxy emulsion and then ultrasonically dispersed. Specifically, 20 to 30 times the weight of water is added to the amino-modified MXene nanosheets, and then stirred at a speed of 400 to 600 rpm for 5 to 10 minutes to obtain a dispersion system, and the dispersion system is ultrasonically treated at the same time. The frequency of the ultrasonic process is 80 to 100 kHz, and the ultrasonic treatment is continued for 5 to 10 minutes after the stirring is completed. The above-mentioned stirring and ultrasonic operation can make the modified MXene nanosheets evenly dispersed, avoiding the adverse consequences of agglomeration and agglomeration of the modified MXene nanosheets due to uneven dispersion when the modified MXene nanosheets are mixed with the aqueous epoxy resin emulsion.
[0032] In the present application, titanium dioxide: can impart hiding power, coloring, and thickness support to the coating.
[0033] Alumina: It has good dispersibility in coatings and can effectively prevent the coating from settling and stratification.
[0034] Polytetrafluoroethylene: can increase the corrosion resistance and wear resistance of the coating.
[0035] In the present application, when the premixed emulsion is mixed with other materials, the stirring rate is 1000 to 1200 rpm and the stirring is performed for 0.5 to 1 h.
[0036] The water-based epoxy resin emulsion in the present application may be a commercially available water-based epoxy resin emulsion (such as an emulsion prepared from epoxy resins E-51, E-55, E-44, etc.), or an water-based epoxy resin emulsion as provided in application number: 202410518939.0 may be used.
[0037] The present application provides a method for preparing a water-based anti-corrosion and wear-resistant coating, which has the following beneficial effects:
[0038] 1) The method of the present application is completed in the water phase when preparing the coating, thereby reducing the emission of organic gases and having the characteristics of being green and environmentally friendly without polluting the environment.
[0039] 2) In the method of the present application, the polytetrafluoroethylene powder added when preparing the coating can improve the anti-corrosion performance of the coating, the added titanium dioxide powder can provide the coating with good hiding power, coloring and thickness support, and the addition of aluminum oxide can improve the dispersion of the coating. The above materials are used in combination with substrate wetting agents, dispersants, defoaming agents, and surface adhesion promoters to make the coating have good stability, hiding power and anti-corrosion performance.
[0040] 3) Modified MXene nanosheets are added to the method of the present application. Since the modified MXene nanosheets have a flaky structure, when they are coated on the surface of a workpiece or an object to be protected, the staggered stacking of these flaky structures can not only increase the strength of the cured coating, but also form a dense protective layer, further reducing the intrusion of oxygen, moisture, etc. into the substrate, thereby achieving protection of the substrate material. When used together with the corresponding ingredients, it can effectively improve the corrosion resistance and wear resistance of the coating.
[0041] 4) The method of the present application has simple operation steps, mild preparation conditions and is easy to implement.
[0042] Optionally, by weight, the aqueous epoxy emulsion is 20 to 50 parts, the polytetrafluoroethylene is 1 to 3 parts, the TiO2 is 2 to 5 parts, the Al2O3 is 2 to 7 parts, the substrate wetting agent is 1 to 3 parts, the dispersant is 0.5 to 3 parts, the defoaming agent is 0.1 to 3 parts, the surface adhesion promoter is 0.1 to 3 parts, the deionized water is 25 to 35 parts, and the curing agent is 3 to 5 parts.
[0043] In the present application, the curing agent includes an amine curing agent, such as aliphatic amine, alicyclic amine, aromatic amine and polyamide. The curing agent should be added before coating (added immediately after use) to prevent premature addition from causing the overall curing of the coating.
[0044] Optionally, the modified MXene nanosheets are prepared as follows:
[0045] Dispersing MXene nanosheets in an ethanol solution, adding a silane coupling agent, reacting at 80-90°C for 24-30 hours, then centrifuging and washing the reaction mixture, and freeze-drying the modified MXene nanosheets obtained by centrifugation for 48-56 hours to obtain modified MXene nanosheets;
[0046] The mass ratio of MXene nanosheets to silane coupling agent is 1:15-30;
[0047] Types of MXene nanosheets include Ti3C2T x -MXene type, Nb2CT x -Mxene type, V2CT x -Mxene type or Mo2CT x -Mxene type.
[0048] In the present application, the ethanol solution is prepared by mixing ethanol and water in a certain volume ratio, and the volume ratio of ethanol to water is 20:1-5.
[0049] In the present application, MXene nanosheets are obtained by intercalation and splitting of accordion-shaped multilayer MXene materials. Specifically, multilayer MXene is placed in a reaction vessel, an intercalation agent is added, and the reaction is stirred at a speed of 1000-1200 rpm at room temperature for 2-24 hours. After the reaction is completed, the MXene is centrifuged at a speed of 3000-4000 rpm for 0.5-1 hour to remove the excess intercalation agent; the intercalated MXene is washed with deionized water for 2-3 times, ultrasonically dispersed for 12-16 hours, and then centrifuged at 3500-4000 rpm to remove the supernatant. The supernatant is freeze-dried for 48-52 hours to obtain MXene nanosheets.
[0050] The mass ratio of the multilayer MXene material to the intercalant is 1:10-12, and the intercalant is one or more of dimethyl sulfoxide (DMSO), tetramethylammonium hydroxide (TMAOH), tetrabutylammonium hydroxide (TBAOH), and ethanol (ET).
[0051] Optionally, the silane coupling agent includes γ-aminopropyltriethoxysilane.
[0052] In the present application, in the process of modifying MXene nanosheets with γ-aminopropyltriethoxysilane, the ethoxy groups in γ-aminopropyltriethoxysilane are hydrolyzed, and corresponding silanol groups are generated in the silane coupling agent. The silanol groups are then condensed with active groups such as hydroxyl groups on the MXene nanosheets, and the silane coupling agent is reacted and grafted on the MXene nanosheets to obtain amino-modified MXene nanosheets. Due to the hydrophilicity of the amino group, it can be well dispersed when mixed into the aqueous epoxy emulsion. And because the amino-modified MXene nanosheet has a flaky structure, when it is applied to the surface of the workpiece or the object to be protected, the staggered stacking between these flaky structures can not only improve the strength of the cured coating, but also this staggered stacking structure can form a dense protective layer, further reducing the intrusion of oxygen, moisture, etc. into the substrate, thereby achieving protection of the substrate material.
[0053] In one achievable manner, the silane coupling agent also includes γ-mercaptopropyl triethoxysilane. When used, γ-mercaptopropyl triethoxysilane and γ-aminopropyl triethoxysilane are mixed to modify the MXene nanosheets, and the two are added in equimolar amounts. The mixed use of γ-mercaptopropyl triethoxysilane and γ-aminopropyl triethoxysilane can improve the anti-corrosion effect, because the addition of γ-aminopropyl triethoxysilane can improve the hydrophilicity of MXene nanosheets and thus improve its dispersion performance in the coating, and the addition of γ-mercaptopropyl triethoxysilane, because the thiol group easily forms a disulfide bond and absorbs oxygen, and can be reduced to a thiol group in a suitable environment (under acidic or reducing conditions), so the mixed use of γ-mercaptopropyl triethoxysilane and γ-aminopropyl triethoxysilane can improve the anti-corrosion effect.
[0054] Optionally, the substrate wetting agent includes one or more of BYK-3400, BYK-3455, and BYK-301.
[0055] In the present application, the substrate wetting agent is a surfactant, and its working principle is to reduce the surface energy of the substrate so that water can spread on the surface of the solid material or penetrate into its surface, thereby wetting the solid material.
[0056] Optionally, the dispersant includes one or more of BYK-154, BYK-021, BYK-028, and BYKJET-9175.
[0057] In the present application, the dispersant is a surfactant, and its main function is to make the various components in the coating evenly dispersed in the system to form a stable suspension.
[0058] Optionally, the defoaming agent includes one or more of BYK-1785, BYK-022, BYK-1724, and BYK-1710.
[0059] In the present application, the role of the defoamer is to eliminate bubbles stirred up during operations such as stirring, thereby stabilizing the coating system.
[0060] Optionally, the adhesion promoter includes one or more of BYK-4509, BYK-4500, and BYK-4513.
[0061] The adhesive has the following advantages: it can significantly improve the bonding strength between resin and various substrates; it can improve the interlayer adhesion between paint topcoat and primer, and improve the moisture resistance, salt spray resistance and heat resistance of the coating film; it is stable in nature and has excellent storage stability and long-term effectiveness in paint and coating systems.
[0062] Optionally, pigments and fillers are also added in step b);
[0063] The amount of pigment and filler added is 1 to 3 parts by weight;
[0064] Pigments and fillers include red iron oxide, molybdenum disulfide or carbon black.
[0065] In the present application, the pigments and fillers can give the coating a corresponding color to enhance the hiding power of the coating. In actual production, pigments and fillers with different colors can be selected according to actual needs.
[0066] In a second aspect, the present application provides a water-based anti-corrosion and wear-resistant coating, which is prepared by any of the methods provided above.
[0067] The characteristics and beneficial effects of the water-based anti-corrosion and wear-resistant coating provided in the present application are as described in the preparation method of the first aspect above, and will not be repeated here. Specific embodiments
[0069] The MXene nanosheets in the following examples were prepared according to the following method:
[0070] Take multilayer MXene (Ti3C2Tx type Ti3C2AlMxene in this application is used as an example) in a reaction container, add intercalation agent TBAOH (wherein the mass ratio of multilayer MXene material to intercalation agent is 1:10), stir at 1000rpm and react at room temperature for 6h, centrifuge at 3500rpm for 0.5h after the reaction, remove excess intercalation agent; wash the intercalated MXene with deionized water for 2-3 times, then ultrasonically disperse for 12h, and then centrifuge at 3500rpm to take out the supernatant. Freeze-dry the supernatant for 48h to obtain MXene nanosheets.
[0071] The water-based epoxy emulsion in the following embodiments and comparative examples adopts the water-based epoxy resin emulsion provided in application number: 202410518939.0.
[0072] Example 1
[0073] A water-based anticorrosion and wear-resistant coating is prepared by the following method:
[0074] S101. Add MXene nanosheets to a reaction container, add ethanol solution (ethanol: water volume ratio is 9:1), ultrasonicate for 20 minutes, then add silane coupling agent (γ-aminopropyltriethoxysilane), react at 80°C for 24 hours, then centrifuge and wash the reaction mixture, and freeze-dry the modified MXene nanosheets obtained by centrifugation for 48 hours to obtain modified MXene nanosheets. The mass ratio of MXene nanosheets to silane coupling agent is 1:15.
[0075] S102, taking 0.5 parts of modified MXene nanosheets by weight, and adding 20 times the weight of water, and then stirring at a speed of 400 rpm for 10 minutes to obtain a dispersed system, and at the same time, ultrasonically treating the dispersed system, the frequency of the ultrasonic process is 80 kHz, and after the stirring is completed, the ultrasonic treatment is continued for 10 minutes to obtain a modified MXene nanosheet dispersed system.
[0076] S103. Add 20 parts of water-based epoxy emulsion by weight to the modified MXene nanosheet dispersion system and stir at 400 rpm for 15 minutes, then add 1 part of polytetrafluoroethylene, 2 parts of TiO2, 2 parts of Al2O3, 1 part of substrate wetting agent (BYK-3400), 0.5 parts of dispersant (BYK-154), 0.1 parts of defoamer (BYK-1785), 0.1 parts of surface adhesion promoter (BYK-4509), 25 parts of deionized water, 3 parts of curing agent (DY-175 water-based epoxy curing agent), 1 part of red iron oxide, continue stirring for 30 minutes, and finally obtain a water-based anti-corrosion and wear-resistant coating.
[0077] Example 2
[0078] A water-based anticorrosion and wear-resistant coating is prepared by the following method:
[0079] S201. Add MXene nanosheets to a reaction container, add ethanol solution (ethanol: water volume ratio is 19:1), ultrasonicate for 30 minutes, then add silane coupling agent (γ-aminopropyltriethoxysilane), react at 90°C for 30 hours, then centrifuge and wash the reaction mixture, and freeze-dry the modified MXene nanosheets obtained by centrifugation for 56 hours to obtain modified MXene nanosheets. The mass ratio of MXene nanosheets to silane coupling agent is 1:30.
[0080] S202. Take 0.5 parts of modified MXene nanosheets by weight, add 30 times the weight of water, and stir at a speed of 600 rpm for 5 minutes to obtain a dispersed system. At the same time, the dispersed system is subjected to ultrasonic treatment. The frequency of the ultrasonic process is 100 kHz. After the stirring is completed, continue to ultrasonicate for 5 minutes to obtain a modified MXene nanosheet dispersed system.
[0081] S203. Add 50 parts of aqueous epoxy emulsion by weight to the modified MXene nanosheet dispersion system and stir at 300 rpm for 20 minutes, then add 3 parts of polytetrafluoroethylene, 5 parts of TiO2, 7 parts of Al2O3, 3 parts of substrate wetting agent (BYK-3400), 3 parts of dispersant (BYK-154), 3 parts of defoamer (BYK-1785), 3 parts of surface adhesion promoter (BYK-4509), 35 parts of deionized water, 5 parts of curing agent (DY-175 water-based epoxy curing agent), and 3 parts of molybdenum disulfide, and continue stirring for 30 to 45 minutes to finally obtain a water-based anti-corrosion and wear-resistant coating.
[0082] Example 3
[0083] A water-based anticorrosion and wear-resistant coating is prepared by the following method:
[0084] S301. Add MXene nanosheets to a reaction container, add ethanol solution (ethanol: water volume ratio is 17:3), ultrasonicate for 25 minutes, then add silane coupling agent (γ-aminopropyltriethoxysilane), react at 85°C for 27 hours, then centrifuge and wash the reaction mixture, and freeze-dry the modified MXene nanosheets obtained by centrifugation for 52 hours to obtain modified MXene nanosheets. The mass ratio of MXene nanosheets to silane coupling agent is 1:25.
[0085] S302, taking 1.0 part of the modified MXene nanosheets by weight, and adding 25 times the weight of water, and then stirring at a speed of 500 rpm for 8 minutes to obtain a dispersed system, and at the same time, ultrasonically treating the dispersed system, the frequency of the ultrasonic process is 90 kHz, and after the stirring is completed, the ultrasonic treatment is continued for 8 minutes to obtain a modified MXene nanosheet dispersed system.
[0086] S303. Add 35 parts of aqueous epoxy emulsion by weight to the modified MXene nanosheet dispersion system and stir at 350 rpm for 18 minutes, then add 2 parts of polytetrafluoroethylene, 3.5 parts of TiO2, 5 parts of Al2O3, 2 parts of substrate wetting agent (BYK-3400), 2 parts of dispersant (BYK-154), 2 parts of defoamer (BYK-1785), 1.5 parts of surface adhesion promoter (BYK-4509), 30 parts of deionized water, 4 parts of curing agent (DY-175 water-based epoxy curing agent), and 2 parts of red iron oxide, and continue stirring for 40 minutes to finally obtain a water-based anti-corrosion and wear-resistant coating.
[0087] Example 4
[0088] A water-based anticorrosion and wear-resistant coating is prepared by the following method:
[0089] S401. Add MXene nanosheets to a reaction container, add ethanol solution (ethanol: water volume ratio is 9:1), ultrasonicate for 30 minutes, then add silane coupling agent (γ-aminopropyltriethoxysilane), react at 80-90°C for 24 hours, then centrifuge and wash the reaction mixture, and freeze-dry the modified MXene nanosheets obtained by centrifugation for 48 hours to obtain modified MXene nanosheets. The mass ratio of MXene nanosheets to silane coupling agent is 1:20.
[0090] S402, taking 1.0 part of the modified MXene nanosheets by weight, and adding 30 times the weight of water, and then stirring at a speed of 400 rpm for 10 minutes to obtain a dispersion system, and at the same time, ultrasonically treating the dispersion system, the frequency of the ultrasonic process is 80 kHz, and after the stirring is completed, continue ultrasonicating for 10 minutes to obtain a modified MXene nanosheet dispersion system.
[0091] S403. Add 35 parts of aqueous epoxy emulsion by weight to the modified MXene nanosheet dispersion system and stir at 400 rpm for 20 minutes, then add 2 parts of polytetrafluoroethylene, 3.5 parts of TiO2, 4.5 parts of Al2O3, 2 parts of substrate wetting agent (BYK-3400), 1.5 parts of dispersant (BYK-154), 1.5 parts of defoamer (BYK-1785), 1.0 part of surface adhesion promoter (BYK-4509), 35 parts of deionized water, 3 parts of curing agent (DY-175 water-based epoxy curing agent), and 2 parts of molybdenum disulfide, continue stirring for 45 minutes, and finally obtain a water-based anti-corrosion and wear-resistant coating.
[0092] Example 5
[0093] A water-based anticorrosion and wear-resistant coating is prepared by the following method:
[0094] S501, the remaining operations are the same as S401, except that the silane coupling agent further includes γ-mercaptopropyltriethoxysilane, and the molar ratio of γ-aminopropyltriethoxysilane to γ-mercaptopropyltriethoxysilane is 1:1.
[0095] S502: Same operation as S402.
[0096] S503: Same operation as S403.
[0097] Comparative Example 1
[0098] D101. The rest of the operations are the same as those in S402, except that no modified MXene nanosheets are added.
[0099] D102: Same operation as S403.
[0100] Experimental example
[0101] The water-based anti-corrosion and wear-resistant coatings prepared in the above-mentioned Examples 1 to 5 and Comparative Example 1 were sprayed on the surfaces of Q235 steel plates and tinplate for performance testing. The thickness of the prepared anti-corrosion coating is 40±2μm. Among them, Q235 steel plates are used as substrates for salt spray tests, and tinplate is used as substrates in other experiments. The coating performance is evaluated by salt spray test (GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test), impact test (GB / T 1732-2020 Paint film impact resistance method), adhesion test (GB / T1720-2020 Paint film circle test), and wear resistance test (GB / T 1768-2006 Determination of wear resistance of paint and varnish rotating rubber grinding wheel method). Among them, the salt spray test does not perform scratch treatment, and the appearance of rust spots on the sample is the test end point. The test results are shown in Table 1.
[0102] Table 1
[0103]
[0104] From the data in Table 1, it can be seen that the water-based coating of the present application has good performance in terms of impact resistance and corrosion resistance.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a water-based anticorrosive and wear-resistant coating, characterized in that: The steps include: a) uniformly mixing the modified MXene nanosheets and the aqueous epoxy resin emulsion to obtain a premixed emulsion; b) adding polytetrafluoroethylene powder, titanium dioxide, aluminum oxide, substrate wetting agent, dispersant, defoamer, surface adhesion promoter, deionized water and curing agent to the premixed emulsion in sequence under stirring, and mixing evenly to obtain a water-based anticorrosive and wear-resistant coating.
2. The method for preparing the water-based anticorrosion and wear-resistant coating according to claim 1, characterized in that: By weight, the aqueous epoxy emulsion is 20-50 parts, polytetrafluoroethylene is 1-3 parts, TiO2 is 2-5 parts, Al2O3 is 2-7 parts, the substrate wetting agent is 1-3 parts, the dispersant is 0.5-3 parts, the defoaming agent is 0.1-3 parts, the surface adhesion promoter is 0.1-3 parts, the deionized water is 25-35 parts, and the curing agent is 3-5 parts.
3. The method for preparing the water-based anticorrosion and wear-resistant coating according to claim 1, characterized in that: The modified MXene nanosheets are prepared according to the following method: Dispersing MXene nanosheets in an ethanol solution, adding a silane coupling agent, reacting at 80-90°C for 24-30 hours, then centrifuging and washing the reaction mixture, and freeze-drying the modified MXene nanosheets obtained by centrifugation for 48-56 hours to obtain modified MXene nanosheets; The mass ratio of the MXene nanosheets to the silane coupling agent is 1:15-30; The types of MXene nanosheets include Ti3C2Tx-MXene, Nb2CT x -Mxene type, V2CT x -Mxene type or Mo2CT x -Mxene type.
4. The method for preparing the water-based anticorrosion and wear-resistant coating according to claim 1, characterized in that: The silane coupling agent includes γ-aminopropyltriethoxysilane.
5. The method for preparing the water-based anticorrosion and wear-resistant coating according to claim 1, characterized in that: The substrate wetting agent includes one or more of BYK-3400, BYK-3455 and BYK-301.
6. The method for preparing the water-based anticorrosion and wear-resistant coating according to claim 1, characterized in that: The dispersant includes one or more of BYK-154, BYK-021, BYK-028, and BYKJET-9175.
7. The method for preparing the water-based anticorrosive and wear-resistant coating according to claim 1, characterized in that: The defoaming agent includes one or more of BYK-1785, BYK-022, BYK-1724 and BYK-1710.
8. The method for preparing the water-based anticorrosive and wear-resistant coating according to claim 1, characterized in that: The adhesion promoter includes one or more of BYK-4509, BYK-4500 and BYK-4513.
9. The method for preparing the water-based anticorrosive and wear-resistant coating according to claim 1, characterized in that: In the step b), pigments and fillers are also added; The amount of the pigment and filler added is 1 to 3 parts by weight; The pigment and filler include red iron oxide, molybdenum disulfide or carbon black.
10. A water-based anticorrosion and wear-resistant coating, characterized in that: The invention comprises a water-based anticorrosion and wear-resistant coating prepared by the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Siloxane modified self-emulsifying waterborne epoxy emulsion and preparation method thereof
CN118307788A
Water-borne photoresponse self-repairing coating material and preparation method thereof
CN110373087A
Method for inhibiting oxidation of MXene nano material and application of MXene nano material in anticorrosive paint
CN114854237A
Anti-corrosion and wear-resistant integrated coating as well as preparation method and application thereof
CN117986972A
Hydrotalcite two-dimensional material-based composite nanofiller and anticorrosive paint
CN118931229A
Cited By
High-precision liquid cooling plate based on 3D printing metal material and preparation process thereof
CN120985258A
High-stability MXene filler and preparation method of high-stability MXene filler in long-acting anticorrosive paint
CN121086567A
Modified wear-resistant anticorrosive resin coating and preparation method thereof
CN121108845A